Trifarotene: A Novel Therapeutic Option for Acne. (27th May 2022) - Naik, Piyu Parth
Abstract : Acne vulgaris, or acne, is a prevailing cutaneous predicament that customarily crops up on the face, neck, and trunk in the forms of comedones, papules, pustules, and nodules. According to epidemiologic explorations, acne affects 9.4% of the global population, making it the eighth most common disease globally. Acne perturbs up to 85% of adolescents, while it is periodically misconceived as an ailment that affects teenagers only; nonetheless, it also affects myriad adults. Acne has well-documented psychosocial ramifications, including adverse effects on self-perception, mental health, and social functioning. Trifarotene is basically a novel fourth-generation locally applied retinoid approved for the first time in the regimens of both face and truncal acnes. The exclusive topical retinoid that adheres precisely to RAR-gamma, the epidermis' most frequent isoform, is trifarotene, approved in October 2019. The current review evaluates the role of trifarotene in treating acne.